Hubungan Pengetahuan Tentang Anemia Dengan Kadar Hemoglobin Remaja Putri di SMAN 05 Pekanbaru - Jannaim; Permanasari, Ika; Wati, Yesi Septina (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2020)
Adolescent girls are vulnerable groups who have a high risk of iron deficiency anemia due to increasednutrient needs at puberty. Adolescent knowledge will influence adolescent behavior in filling iron-rich foodsand in the end have effect on adolescent hemoglobin levels. The purpose of this study was to determine therelationship of knowledge about anemia with hemoglobin levels in adolescent girls at Senior High School of 05Pekanbaru. This type of research was correlational with cross sectional approach. The study was conductedfrom March-September 2019 to 52 adolescent girls. The sampling technique used purposive sampling method.The instrument of data collection used a questionnaire to determine the knowledge of adolescent girls aboutanemia and Hb test to determine hemoglobin levels in adolescent girls Data analysis used Pearson correlationtest. The results showed that the average age of adolescent girls was at the age of 16 years with an averagehemoglobin level of 13.8g / dl. There was a relationship between adolescent girls' knowledge with hemoglobinlevels in adolescent girls at Senior High Scholl of 05 Pekanbaru (p = 0.041, p <0.05). Based on these results, itis expected to increase adolescent knowledge to be better through sustainable health education programs thatare more easily accepted by youth groups